PERAN PERSONALIZED MARKETING DALAM KEGIATAN PEMASARAN BISNIS ONLINE - GUNAWAN, CANDRA (Kajian Ilmiah Mahasiswa Manajemen, 2012)
The rapid economic growth in the current push but unfortunately the increasing number of marketers do not market share has increased significantly, making this the marketers face stiff competition. Personalized web-based marketing using consumer preference information to make adjustments in order to match the offer needs of Internet users. Information can be obtained consumer marketers easily through cookies, browsing history, registration forms and online surveys. Personalized web-based marketing can reduce the cost of direct mail production to near zero, this leads to the marketers do not need print the letter and sent it back to each consumer. Personalized web-based marketing can be a competitive advantage, especially in the marketers internet marketing. Personalized web-based marketing is important, because personalized web-based marketing can reduce the provision of information or offers that are not useful for consumer, making it look simple and attractive website. Personalized web-based marketing will create a dialogue between marketers and consumers an effective and mutually satisfying. Personalization is expected to be a strong commitment between consumers and marketers, there by strengthening customer loyalty.